Structure and content of administrative and legal status of the subjects counteracting offenses in the field of entrepreneurial activity - V. M. Vasyliev (Law and Safety)
Theoretical approaches to the definitions of “legal status”, “administrative and legal status” have been established. The elements of administrative and legal status of the subject counteracting offense in the sphere of entrepreneurial activity have been determined and analyzed. The main powers of the state agencies that accomplish control activity over the subjects of entrepreneurial activity have been characterized. The notion of a subject of an offense in the sphere of entrepreneurship has been defined: a system of state and non-state agencies, public organizations, social groups and citizens whose activities are focused on eliminating the causes and conditions that give rise to and provoke offenses in the sphere of economic commercial activity (entrepreneurship), preventing these offenses at different stages of incorrect behavior of the participants of relations in the field of entrepreneurship, as well as bringing them to legal liability. Besides, the above subjects have been systematized in this study and their range has been determined. The main ones have been highlighted: the President of Ukraine, Verkhovna Rada of Ukraine, the Cabinet of Ministers of Ukraine; local governments; Ministry of Finance of Ukraine; Ministry of Economic Development and Trade of Ukraine; State Fiscal Service and its structural units (except customs control at the border); State Inspectorate of Ukraine; National Bank of Ukraine; revenue and fees authorities of Ukraine. The author has defined a special group of subjects, those who have administrative and jurisdictional powers.